Analysis of commercial approach to non-organic domestic waste management at settlement besides Kampar River case study : Pulau Birandang Village and Alai Village in Kampar District, Riau Province, Indonesia - Yelna Yuristiary; Rahman Raeyani Kalele; Yusuf Abdurachman (Syiah Kuala University, 2013)
The area of coverage of waste management services in some areas sometimes only focus on specific areas such as the capital province, district or city. Some areas of the region (district) still do not get special attention for waste management facilities services from local City Sanitation Department. In this study we raised two villages located on the banks of the Kampar River and examined the management of non-organic domestic waste in this area. We choose Pulau Birandang Village and Alai Village because of the habit this people to throw garbage like non-organic waste (such as paper, plastics, etc) to the Kampar river. This act is very dangerous for the sustainability of water security and can cause silting rivers. The aims of this research to analyze the influence of commercial approach as a solution to solve waste problem in both villages. Commercial approach is the method applied by giving incentives to people who are sort the non-organic waste according to its kind. Data for this study were collected from observation using 80 questionnaires to 80 respondents from both villages, the Pulau Birandang village and Alai village. Results of the analysis is also reinforced by opinión from the leaders of them (people) who are likely to reflect the wishes of the people too. The results from this study is the commercial approach (take and give system) which applied in this villages could increase people's enthusiasm in managing domestic waste by sorting waste before it is collected.